2020
DOI: 10.1038/s41598-020-68484-3
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of autophagy by low concentration of salicylic acid delays methyl jasmonate-induced leaf senescence

Abstract: Crosstalk between salicylic acid (SA) and jasmonic acid (JA) signaling plays an important role in regulation of plant senescence. our previous work found that SA could delay methyl jasmonate (MeJA)-induced leaf senescence in a concentration-dependent manner. Here, the effect of low concentration of SA (LCSA) application on MeJA-induced leaf senescence was further assessed. High-throughput sequencing (RNA-Seq) results showed that LCSA did not have dominant effects on the genetic regulatory pathways of basal met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…This result indicates that hormones such as jasmonic acid, abscisic acid, and brassinosteroids are produced early in DLS-91—at 0 DDT, whereas salicylic acid is produced during dark treatment (1 DDT) in this genotype. Consistent with these findings, Yin et al [ 60 ] have suggested that SA delays leaf senescence by regulating concentrations of methyl jasmonates. In Arabidopsis, ABI5 has been determined to delay DLS [ 61 ].…”
Section: Resultssupporting
confidence: 57%
“…This result indicates that hormones such as jasmonic acid, abscisic acid, and brassinosteroids are produced early in DLS-91—at 0 DDT, whereas salicylic acid is produced during dark treatment (1 DDT) in this genotype. Consistent with these findings, Yin et al [ 60 ] have suggested that SA delays leaf senescence by regulating concentrations of methyl jasmonates. In Arabidopsis, ABI5 has been determined to delay DLS [ 61 ].…”
Section: Resultssupporting
confidence: 57%
“…Moreover, the significant increase only in SA at 48 HAI in susceptible plants, when compared to resistant and control plants, can suggest an antagonist crosstalk between SA and JA-ME. Similarly, a negative crosstalk between SA and JA-ME has been reported in other plant defence responses [ 58 ].…”
Section: Discussionmentioning
confidence: 71%
“…These results indicated the presence of an undetectable cell population by Annexin-V and suggested that both cells should be evaluated for positivity of other cell death mechanisms. MJ was previously reported for its inducer role for autophagy ( Zhang et al, 2016 ; Yin et al, 2020 ). Therefore, we further focused on 24-h C-10 treatment–based enrichment of autophagy in GBM cells.…”
Section: Resultsmentioning
confidence: 90%